Methodological Aspects of Scientific Research - Beev, Ivaylo (Research Papers, 2025)
This article examines the question of the scientific nature of scientific research. There are two specific methodological problems that need to be addressed: falsification/verification and, in part, the problem of induction, which is based mainly on Karl Popper's approach.
Keywords: Verification; Induction; Popper